Acetylcholine receptor in a C2 muscle cell variant is retained in the endoplasmic reticulum (The Rockefeller University Press, 1989)
We have examined the properties and intracellular localization of acetylcholine receptors in the C2 muscle cell line and in a variant (T- ) that accumulates AChR intracellularly. On immunoblots, the subunit structures of the AChR from wild-type and T- cells were similar except that the gamma and delta subunits of the variant AChR had altered mobilities. Digestion with endoglycosidases H and F demonstrated that this difference results from a failure of high-mannose N-linked oligosaccharides on AChR subunits to be processed to complex forms in the variant. N-linked glycosylation of other proteins in the variant was normal. When examined by immunocytochemistry, the distribution of internal AChR in wild-type cells was consistent with a location both in the endoplasmic reticulum and in the Golgi. Variant cells, however, showed no evidence of Golgi staining. Subcellular fractionation experiments also demonstrated AChR in the Golgi fractions of wild-type cells, but not in those derived from T- cells. We conclude that in T- myotubes most of the AChR fails to be transported out of the endoplasmic reticulum.